The relationship between colonic diverticulosis and abdominal visceral and subcutaneous fat accumulation measured by abdominal CT scan - Lee, Sang Pyo; Woo Ahn, Yong; Young Lee, Oh; Nyeong Lee, Kang (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Besides age, risk factors for colonic diverticular disease include dietary meat intake and Western lifestyles, which are also risk factors for obesity. However, the association between obesity and colonic diverticular disease, including diverticulosis and diverticulitis, is not well established. The aim of this study was to investigate the relationship between colonic diverticulosis and obesity using abdominal fat quantified by abdominal CT scan and lipid profiles, as well as body mass index (BMI). Materials and Methods: In this study based on a retrospective case note review, we enrolled 133 subjects (control group (n=55), diverticulosis group (31), and diverticulitis group (47)). Abdominal fat areas (total abdominal fat, visceral fat, subcutaneous fat) were quantified by abdominal CT scan. Serum lipid profiles and BMI were checked. Statistical analysis was performed by independent t-tests, with significance set at p<0.05. Results: In the diverticulosis group, total abdominal fat area, visceral fat area, and abdominal subcutaneous fat area were all larger than those of the control and diverticulitis groups. In the diverticulitis group, total cholesterol, high density lipoprotein (HDL), low-density lipoprotein (LDL), and BMI were lower than in the control and diverticulosis groups. There were no significant differences between the three groups in visceral-to-subcutaneous abdominal fat ratios and serum triglyceride levels. Conclusion: In conclusion, obesity may predispose one to occurrence of colonic diverticulosis. Abdominal fat measurement by CT scan may be a good method of assessing risk of colonic diverticular disease.